2022
DOI: 10.58258/jime.v8i4.4014
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Factors Influencing Efl Students’ Critical Thingking Skill and Reading Achivents in Reading Classroom

Abstract: This study aims to investigate the factors that influence EFL students' critical thinking skills and reading achievement in reading classroom. To achieve the research objectives, so that the design of this research was a case study by taking 30 students at third semesters who program critical reading in English Study Program at the Faculty of Culture, Management and Business, Mandalika University of Education. The students were given critical thinking skill test in the form of reading an article and questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Further comprehensive research is necessary to clarify the effects of AI capabilities. The factors affecting critical thinking are diverse [28], including general selfefficacy [29], learning motivation [30], cognition [31], emotional intelligence [32], and the environment [33]. Previous studies have shown that general self-efficacy and learning approaches play a crucial role in developing critical thinking skills [34].…”
Section: Scenarios Of Ai Education Ai-related Technologymentioning
confidence: 99%
“…Further comprehensive research is necessary to clarify the effects of AI capabilities. The factors affecting critical thinking are diverse [28], including general selfefficacy [29], learning motivation [30], cognition [31], emotional intelligence [32], and the environment [33]. Previous studies have shown that general self-efficacy and learning approaches play a crucial role in developing critical thinking skills [34].…”
Section: Scenarios Of Ai Education Ai-related Technologymentioning
confidence: 99%